Application of a magnetic molecularly imprinted polymer for the selective extraction and trace detection of lamotrigine in urine and plasma samples. Issue 13 (2nd May 2014) - Behbahani, Mohammad; Bagheri, Saman; Amini, Mostafa M.; Sadeghi Abandansari, Hamid; Reza Moazami, Hamid; Bagheri, Akbar
<x xml:space="preserve">Abstract</x> Magnetic molecularly imprinted polymers have been synthesized for the selective preconcentration and trace determination of lamotrigine (LTG) in urine and plasma samples. The magnetic nanoparticles were modified by tetraethyl orthosilicate and 3‐methacryloxypropyl trimethoxysilane before imprinting. The magnetic molecularly imprinted polymers were prepared via surface molecular imprinting technique, using Fe3O4 as a magnetic component, LTG as template molecule, methacrylic acid as a functional monomer, ethylene glycol dimethacrylate as a cross‐linker, and 2, 2′‐azobisisobutyronitrile as a radical initiator in methanol/acetonitrile (50:50, v/v) as the porogen. The obtained sorbent was characterized using scanning electron microscopy, Fourier‐transform infrared spectroscopy, X‐ray diffraction, and thermal analysis. Separation of the sorbent from the sample solution was simply achieved by applying an external magnetic field. Determination of the extracted drug was performed by high‐performance liquid chromatography with UV detection. Under the optimum extraction conditions, the method detection limits were 0.7 μg/L (based on S/N of 3) for urine samples and 0.5 μg/L for plasma samples. A linear dynamic range of 1–1000 μg/L was obtained for LTF in plasma and urine samples. Finally, the applicability of the proposed method was evaluated by extraction and determination of LTG in urine and plasma samples.